Introduction to Managerial Accounting - Charles Horngren (Pearson Education Limited, 2024)
Introduction to Management Accounting helps to enhance readers' ability to make effective economic decisions by encouraging them to understand the inner-workings of the concepts, rather than solely focusing on technique memorization.